Analisis Kemampuan Pemecahan Masalah Mahasiswa ditinjau Dari Kecemasan Matematis - Putri Yulia; Silva Amelia; Eline Yanty Putri Nasution (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2025)
This study aims to analyze the problem-solving abilities of Mathematics Education students at IAIN Kerinci in relation to their levels of mathematics anxiety. Mathematics anxiety is a significant barrier that interferes with cognitive processes and impairs academic performance in mathematics learning. Employing a qualitative approach, data were collected through questionnaires, documentation, and problem-solving tests on systems of linear equations, analyzed using Polya’s problem-solving stages. The results revealed that students with high anxiety faced difficulties in almost all stages, those with moderate anxiety showed partial understanding but lacked execution accuracy, while students with low anxiety demonstrated optimal performance across all stages. The study proposes the Qurmatica approach as a pedagogical solution that integrates spiritual values to reduce anxiety and enhance learning motivation.